The Bilsk fortified settlement and the Hallstatt world - Shramko, Iryna; Zadnikov, Stanislaw (Uniwersytet Wrocławski Instytut Archeologii, 2021)
The Bilsk fortified settlement, the largest in Europe of the Early Iron Age (8th–4th centuries BC), located onthe left bank of the Dnieper, demonstrates links with the Hallstatt culture, Greek civilization and nomadic Scythianculture, starting from the second half of the 7th century BC. The article discusses one of the vectors of cultural in-fluences from the Hallstatt world, traced on the basis of long-term excavations. In the material culture of the secondhalf–late 8th–first half of the 7th century BC, the influence of the Basarabi cultural complex is most noticeable, and inthe second half of the 7th–6th centuries BC the impact of the cultures and cultural groups of the East Hallstatt Circle.As a result of migration processes in the local environment, objects of western types became widespread, Hallstattimports are also known. In the domestic and sacred sphere, the society also borrowed some ideas. New data thatsignificantly expanded our understanding of the nature and degree of the Hallstatt influence on the local sedentarypopulation was obtained as a result of excavations in 2013–2019 mound necropolis Skorobir